Does Math Anxiety Influence Students’ Self-Regulated Learning? A Predictive Relationship Study at Two Vocational Schools at Bandung Regency - Nurhayati, Ida; Akbar, Muhamad Fijar Rotul; Putra, Harry Dwi; Fitriani, Nelly (IKIP Siliwangi, 2024)
While mathematics is immensely imperative and regarded as a fundamental subject serving as one of the graduation requirements at every level of education in Indonesia, including vocational schools, adverse perceptions associated with it as a challenging subject are deeply ingrained in society, particularly among students. Despite there is a wealth of research exploring math anxiety and elf-regulated learning, a discernible gap exists in the literature, specifically within the Indonesian context, particularly among Vocational Students in the Bandung area. This research aims to explore the predictive relationship between math anxiety and students' self-regulated learning within the context of vocational education. Employing linear regression statistical analysis, and survey data collection method, this quantitative study involved 99 participants from two vocational schools in Bandung Regency. The results indicate a statistically significant impact of math anxiety on students' self-regulated learning. However, it's noteworthy that the degree of correlation is considered low. Furthermore, no significant differences were identified concerning variables such as age, sex, streaming, and class level. These findings contribute to the understanding of the dynamics between math anxiety and self-regulated learning, particularly within the context of vocational education in the Bandung region, and can serve as a valuable insight for future research in similar topics.